The information content of M3 for future inflation - Carmine Trecroci; Juan Luis Vega (European Central Bank (ECB), 2000)
The information content of broad money M3 for future GDP inflation in the euro area is investigated from a number of perspectives. Firstly, tests that money does not Granger-cause prices are conducted within a cointegrated VAR system comprising real M3 holdings, real GDP, inflation and short- and long-term interest rates. Secondly, this empirical framework is extended to investigate the claim that - in the context of an extended P-star model - the real money gap has substantial predictive power for future inflation. And thirdly, the P-star type of model developed is compared with an existing rival model of inflation in the euro area where no explicit role is given to monetary developments. Our empirical results confirm that a significant positive association exists between the real money gap and future inflation up to five to six quarters ahead, reaching a maximum at the three-to-four quarter horizon. It is also shown that, although the extended P-star model outperforms the competing model in terms of out-of-sample forecast accuracy (as measured by the root mean square forecast errors) at horizons above two quarters, the hypothesis that no useful information is contained in rival evidence can be rejected at standard confidence levels.
Keywords: C32; C50; E30; E40; 330; euro area; inflation; leading indicators; M3; monetary aggregates; P-star